The complete idiot's guide to running - Rodgers, Bill, 1947-; Douglas, Scott (Indianapolis, IN : Alpha, 2010)
Take the intimidation out of running. This guide is packed with tips and techniques on everything from getting started to more advanced methods of training.
In the beginning. Hit the road, Jack and Jill ; Run for the health of it ; Taking your first steps ; Strutting your stuff: where to run ; Morning, noon, or night: when to run ; Mo' better motivation -- The right stuff. Sole mates: finding the right running shoes ; From top to bottom: the right running apparel ; Gadgets on the go -- Body shop. Stretching: the truth ; Pumped up: strength training for runners ; The aches and the pains ; Eating on the run: deciding on your diet ; Crossing the divide: cross-training for runners ; For women only ; Weathering the elements -- Join the human race. The finish line: why you should race ; The racing circuit ; Basic training for racers ; Short but sweet: 5ks to 10ks ; Middle ground: 15ks to half-marathons ; In it for the long run: the marathon ; Roots, rocks, and ruts: trail running -- Running through the ages. Kidding around: running for children ; Late in the race: advice for senior runners ; Running for your life.
Includes bibliographical references (p. [303]-306) and index.
Keywords: Jogging -- Handbooks, manuals, etc; Running -- Handbooks, manuals, etc; Jogging -- Handbooks, manuals, etc; Running -- Handbooks, manuals, etc